2019
DOI: 10.1521/jscp.2019.38.10.811
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Preference to Avoid or Seek Help in Person and Online Among College Students with Suicidal Ideation

Abstract: Suicidal thoughts, for which college students are at risk, tend to be negatively associated with intentions to seek therapy, particularly among collegeaged men. Emerging research suggests college students may seek psychological help online; however, factors that explain why they avoid help and/or may prefer online help remain unknown. Method: 816 college students completed measures of suicidal ideation, help-seeking intentions, and theoretical mediators and moderators of their relationship. Results: Suicidal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Other online suicide prevention resources tailored for men have also shown promise, including one from Australia called Man Up , a well‐received and widely shared Facebook‐based health promotion campaign that engaged men in dialogue around masculinity and suicide (Schlichthorst et al, 2019). However, Wilks et al (2019) found that for some males at risk for suicide, they may not prefer online assistance as a method of support, at least as much as females do.…”
Section: Discussionmentioning
confidence: 99%
“…Other online suicide prevention resources tailored for men have also shown promise, including one from Australia called Man Up , a well‐received and widely shared Facebook‐based health promotion campaign that engaged men in dialogue around masculinity and suicide (Schlichthorst et al, 2019). However, Wilks et al (2019) found that for some males at risk for suicide, they may not prefer online assistance as a method of support, at least as much as females do.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prevention programs often market themselves as programs to help individuals cope with "stress" or "better manage emotions," and shy away from the use of diagnostic labels or pathologizing language. Additionally, as many emerging adults show a preference for seeking help online (e.g., Wilks et al, 2019), digital prevention programs could represent a first step for emerging adults who are looking for help to manage their symptoms but are not ready to seek formal in-person treatment. This stepped-care approach could capitalize on emerging adults' help-seeking preferences and represent a way to engage individuals in one type of psychological support that could help address psychological symptoms (or target underlying mechanisms).…”
Section: Discussionmentioning
confidence: 99%
“…Although online interventions have been shown to be effective in this review, it should be considered that some men at risk of suicide may not prefer online support, at least as much as women do [35]. Men traditionally view asking for help as non-masculine; however, further intervention studies are required to identify the impact of web-based methods on men's search for help [29].…”
Section: Addressing Masculinity and Gender Normsmentioning
confidence: 95%